Relevansi Strategi Pembelajaran dengan Karakteristik Materi Pokok MI/SD - Indah Hari Utami (LP2M STIT Palapa Nusantara, 2020)
With the learning strategy, students are expected to be easier in the reply taught by the teacher. Because in the curriculum 2013 students are required to be more active, creative, innovative teachers only as facilitators in the process of learning to teach. The objective of the learning strategy is to align the basic ability of children optimally where teachers emphasize the activities and creativity and character of children so that the learning process or learning is more quality. This article aims to analyse the relevance of the learning strategy with the characteristics of the MI/SD staple in the class IV thematic Book 1 sub theme 1. The method of research used is quality that is descriptive. The data sources in this study use primary data sources in the form of thematic books (book Teachers and book students) class IV SD/MI Theme 1 sub theme 1. The method used is library Research. The result of this research is to know the relevance of the learning strategy with the main material MI/SD in theme Book Class IV thematic 1 sub Theme 1.